Synthesis and characterization of hindered amine light stabilizers based on end functionalization of polypropylene - Reddy, K. Raghunatha; Kumar, Bijendra; Rana, Sravendra; Tevtia, Amit K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
A polymeric hindered amine light stabilizer (HALS), where HALS moiety was attached at the terminal end of the polypropylene chain via end-functionalized vinylidine PP through simple organic reactions, was synthesized. It comprises the synthesis of vinylidine-terminated polypropylene by using Cp2ZrCl2/MAO as catalyst system and epoxidation of vinylidene polypropylene. The final product was synthesized by carrying out the reaction between epoxy end functionalized polypropylene and 4-amino-2,2,6,6-tetrametyl piperidine. The final product was characterized by using H-1 NMR, C-13 NMR, and FT-IR spectra. Functionality was calculated by using vapor phase osmometry and H-1 NMR. The solubility and diffusion coefficient of the product were calculated and also its stabilization performance was checked. (c) 2007 Wiley Periodicals, Inc.
Keywords: end functionalization; functionalization of polymers; polymeric HALS; polypropylene; vinylidine and photostabilization